2015
DOI: 10.1097/hjh.0000000000000468
|View full text |Cite
|
Sign up to set email alerts
|

Swimming training prevents alterations in ecto-NTPDase and adenosine deaminase activities in lymphocytes from Nω-nitro-L-arginine methyl ester hydrochloride induced hypertension rats

Abstract: These findings highlight the link between purinergic signalling and inflammatory process and suggest a novel mechanism in which moderate aerobic exercise possesses the potential to attenuate inflammation caused by hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
2
18
0
1
Order By: Relevance
“…In contrast, regular exercise training has been associated with a significant protection against immuno-inflammatory process. Its protective effect is due to the ability to enhance mitochondrial performance and to prevent the ATP release and then the inflammasome activation [7,25]. Corroborating with these findings, we observed that the regular exercise training was able to restore the metabolic and inflammatory homeostasis as well as to reverse the alterations observed in E-NTPDase and ADA activities of lymphocytes in MetS patients.…”
Section: Discussion ▼supporting
confidence: 78%
See 2 more Smart Citations
“…In contrast, regular exercise training has been associated with a significant protection against immuno-inflammatory process. Its protective effect is due to the ability to enhance mitochondrial performance and to prevent the ATP release and then the inflammasome activation [7,25]. Corroborating with these findings, we observed that the regular exercise training was able to restore the metabolic and inflammatory homeostasis as well as to reverse the alterations observed in E-NTPDase and ADA activities of lymphocytes in MetS patients.…”
Section: Discussion ▼supporting
confidence: 78%
“…Then, by controlling the extracellular adenine nucleotide and nucleoside levels, ectonuclotidase enzymes, such as E-NTPDase and ADA, are able to regulate the immune homeostasis and, for this reason, alteration in their activities has been associated with inflammatory diseases [1]. Indeed, studies of our research group have demonstrated alteration in the ectonucleotidase enzymes of lymphocytes in diseases that have inflammatory process involved in their pathology, such as hypertension [7], multiple sclerosis [26,30], HIV [19] and smoking [33]. Similarly, the inflammatory process appears to be a central mechanism in the pathophysiology of the MetS, since in central obesity the adipose tissue becomes metabolically active and releases different adipocytokines, which regulate immune-inflammatory function and may contribute to the development of chronic inflammation, insulin resistance and NAFLD [22,35].…”
Section: Discussion ▼mentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations of these parameters were minimized or returned by CR and EX. Several studies have showed beneficial effects of short-term CR and EX for reversing of these changes [16][17][18][19][20]. The human body also accumulates ROS that lead to tissue damage and decreased cardiovascular hemodynamic.…”
Section: Cardiovascular Hemodynamicmentioning
confidence: 99%
“…This fact can be explained because ATP, released from sympathetic nerves, along with norepinephrine (NE) and neuropeptide Y, can activate P2X receptors at postjunctional membranes evoking vascular smooth muscle contraction, which generally potentiate the effects of NE at α 1-adrenoceptors [ 51 , 80 ]. Accordingly, Cardoso et al have shown that E-NTPDase 1 expression and activity have the ability to control the effects of sympathetic nervous system in the vasculature [ 81 ].…”
Section: Noncommunicable Neurological and Degenerative Diseasesmentioning
confidence: 99%